No evidence for loss of natalizumab effectiveness with every-6-week dosing: a propensity score–matched comparison with every-4-week dosing in patients enrolled in the Tysabri Observational Program (TOP). (September 2021) - Butzkueven, Helmut; Kappos, Ludwig; Spelman, Tim; Trojano, Maria; Wiendl, Heinz; Su, Ray; Liao, Shirley; Hyde, Robert; Licata, Stephanie; Ho, Pei-Ran; Campbell, Nolan
Background: Extended interval dosing of natalizumab is associated with significantly lower progressive multifocal leukoencephalopathy risk compared with every-4-week (Q4W) dosing in patients with relapsing-remitting multiple sclerosis. Previous studies have suggested that natalizumab effectiveness is maintained in patients who switch from Q4W to extended interval dosing but have been limited by a lack of well-matched patient cohorts. Methods: Tysabri Observational Program (TOP) data as of November 2019 were used to identify patients with relapsing-remitting multiple sclerosis treated with natalizumab Q4W and those with a single physician-indicated dosing change from Q4W to every-6-week (Q6W) dosing after ⩾1 year of Q4W treatment. Patients were propensity score matched at the time of the switch from Q4W to Q6W dosing. Clinical outcomes (annualized relapse rate and probability of remaining relapse free or free of 24-week confirmed disability worsening) and safety outcomes were assessed for the two cohorts. Results: This study included 219 pairs of propensity score–matched Q6W and Q4W patients. Annualized relapse rates were similar for Q6W (0.150) and Q4W (0.157) patients. The probability of remaining relapse free [hazard ratio = 1.243 (95% confidence interval = 0.819–1.888); p  = 0.307] and of remaining free of 24-week confirmed disability worsening [hazard ratio = 0.786 (95% confidence interval = 0.284–2.176); p  = 0.644] did not differ significantly between Q6W and Q4W patients. Summarized safety results for the matched Q6W and Q4W patients are also presented. Conclusion: These real-world findings in well-matched patient cohorts from TOP demonstrate that natalizumab effectiveness is maintained in patients who switch to Q6W dosing after ⩾1 year of Q4W dosing. ClinicalTrials.gov identifier: NCT00493298